Estimativa da densidade dos perfis de corpos celulares de neurônios na amígdala central e hipotálamo lateral e avaliação comportamental de camundongos sob o uso de esteroides anabolizantes - Passos, Juliane De Lima (2014)
This experimental study evaluated the behavioral and neuronal effect of two Anabolic-Androgenic Steroids (AAS) administration, testosterone cypionate (Deposteron®) and stanozolol (Winstrol Depot®), which are indistinguishably used by gym customers in hyperphysiologic doses. Usingallometric extrapolation, intraperitoneal (IP) daily doses of 0.8mg/kgDeposteron® and 1.8mg/kg Winstrol Depot® were administered to male and female Swiss mice, in comparison to a control group treated with daily 0.04ml saline solution. All animals were submitted to swimming exercise during experiment time in order to simulate physical activity. By means of estimated profile analyses of neuron cell bodies density, results showed statistically significant decrease of neuron cell bodies number in lateral hypothalamus area of both male and female animalsaswell as in central amygdaloid area of female ones after AAS administration. The outcomes indicated that these two AAS can generate neuronal damage and impaired functions in these brain structures. Aggressive behavioral tests analyses were performed by resident-intruder paradigm and proved to be no statistically significant. Nevertheless, all resident-treated animals displayed an aggressive behavior; in contrast to a dominant attitude of resident animals, intruder ones presented themselves with a compliant and neutral attitude. For all that, we believe this study to be scientificallyimportant due to the scarcity of quantitative morphologic researches concerning AAS and it alsoshows that AAS abuse lead to neuronal loss and consequent activity impairment. In our opinion, further studies are necessary because of controversies about AAS use and aggressive behavior relationship.